Variations in moisture content and its effect on the shrinkage of Gigantochloa scortechinii and Bambusa vulgaris at different height of bamboo culm - Anokye, Rogerson; Kalong, Regina Maria; Bakar, Edi Suhaimi; Ratnasingam, Jegatheswaran; Awang, Khairul (Indonesian Wood Research Society, 2014)
The advancement of technology throughout the world has made bamboo one of the popular raw materials in the wood-based industry and has recently been considered as an engineering material. Malaysia has a good number of bamboo species but few that can be utilised commercially. Unfortunately, Malaysia still lacks some basic information about the properties of bamboo, especially on local bamboo species. This study provides a basic and details information about some physical properties of two the most popular local bamboo species, Gigantochloa scortechinii and Bambusa vulgaris. The study covered moisture content variation at different heights at both nodal and internodal portions of the bamboo culm. Comparison between the portions and between the nodes and internodes as well as between the species were carried out which showed significantly, no difference among the MC along the bamboo culm. The shrinkage at the three perpendicular axis directions showed that the radial shrinkage was slightly greater than tangential and was much greater than in longitudinal direction. Nodes appeared to have lower moisture content and high percentage of shrinkage compared to internodes. These variations were expected to be related with the anatomical structure different between the two categories of the bamboo culms.